Manajemen Risiko dalam E-Bisnis: Pendekatan untuk Keamanan Data dan Mitigasi Risiko Siber - Ari Susanto (PUTRA JAWA PUBLISHER, 2024)
Risk management in e-business is one of the important aspects in facing the increasingly complex challenges of data security and cyber threats. This article discusses a strategic approach to risk management to protect data, maintain customer trust, and ensure operational sustainability. The research covers risk identification, impact analysis, and the implementation of technology and policy-based mitigation solutions. By emphasising the importance of risk management integration in e-business, this article provides guidance for companies to build a resilient security framework, while meeting global compliance standards. The results are expected to support the development of a secure and reliable e-business ecosystem.